Maps for Health Metrics: An Epidemiology Resource Webliography - Rachel DeBoer; Susan Ward Aber (Issues in Science and Technology Librarianship)
Maps have a long history of being used as sources to track disease outbreaks, link causes and effects of disease, combat misinformation, present ideas and improve patient care. This webliography is a compendium of thematic maps, including health metrics, risk factors, infectious diseases, cancers, chronic diseases, and psychiatric disorders. Maps were gathered after evaluating data for reliability and currency. These selective epidemiology resources may aid public health professionals, medical practitioners, researchers, and librarians, who serve an information-seeking clientele interested in health-related quality of life.